2021
DOI: 10.1002/adhm.202001997
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Mfsd2a‐Mediated Low Transcytosis to Boost Nanoparticle Delivery to Brain for Chemotherapy of Brain Metastases

Abstract: Microvessels of the blood–brain barrier (BBB) exclusively express the major facilitator superfamily domain‐containing protein 2a (Mfsd2a), which is the key transporter for docosahexaenoic acid uptake into the brain. Mfsd2a suppresses caveolae‐mediated transcytosis to regulate BBB transcellular permeability via controlling lipid composition of BBB endothelial cells. It is speculated that Mfsd2a can restrain BBB crossing efficiency and brain accumulation efficiency of brain‐targeting drug delivery systems, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Human brain-seeking breast cancer MDA-MB-231Br cells (231Br) were gifted by Dr. Patricia Steeg at the NCI and extensively used in our previously published papers. ,, Both 231Br cells and bEND.3 cells (mouse BBB endothelial cells, ATCC) were grown in the complete DMEM medium with fetal bovine serum (10%), penicillin (100 units/mL), and streptomycin (100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human brain-seeking breast cancer MDA-MB-231Br cells (231Br) were gifted by Dr. Patricia Steeg at the NCI and extensively used in our previously published papers. ,, Both 231Br cells and bEND.3 cells (mouse BBB endothelial cells, ATCC) were grown in the complete DMEM medium with fetal bovine serum (10%), penicillin (100 units/mL), and streptomycin (100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…h DOX@NPs were assembled using poly­(lactic-co-glycolic acid)-poly­( ε -carbobenzoxy- l -lysine) as the starting material through a double-emulsion solvent evaporation technique. ,, Typically, the internal aqueous phase (20 mg of h DOX dissolved in 0.2 mL of water) was added drop by drop into the organic phase under vortex (100 mg of starting material dissolved in 2 mL of ethyl acetate) and sonicated to form the water/oil emulsion. The water/oil emulsion was added drop by drop into the external aqueous phase under vortex (4 mL of 2.5% polyvinyl alcohol 403, Kuraray) and sonicated to form water/oil/water emulsion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another difficult challenge in glioma treatment is to overcome the BBB, which could be resolved with the advent of nano-based drug delivery system (NDDS) 33 , 34 , 35 , 36 . Polymer micelle is a commonly used nano-delivery system, which can enhance the water solubility of drugs, reduce the phagocytosis of the reticuloendothelial system and prolong drug circulation time 37 , 38 , 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have identified nanomedicine as an ideal approach to improve the efficiency and wound treatment. 3 Nanoparticles are ultrafine particles between 1–1000 nm in diameter, 8 that have many advantageous properties related to trauma therapy, including being biodegradable, exhibiting controlled drug release, enough drug delivery efficacy, 10 have healing properties, penetrated blood-brain barrier 11 and their ability to be used as an extracellular matrix material. 3 Many studies have shown that nanoparticles can improve antibacterial and wound-healing activities.…”
Section: Introductionmentioning
confidence: 99%